Comprehensive multiphase NMR applied to a living organism - Mobarhan, Yalda Liaghati (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Comprehensive multiphase (CMP) NMR is a novel technology that integrates all the hardware from solution-, gel- and solid-state into a single NMR probe, permitting all phases to be studied in intact samples. Here comprehensive multiphase (CMP) NMR is used to study all components in a living organism for the first time. This work describes 4 new scientific accomplishments summarized as: (1) CMP-NMR is applied to a living animal, (2) an effective method to deliver oxygen to the organisms is described which permits longer studies essential for in-depth NMR analysis in general, (3) a range of spectral editing approaches are applied to fully differentiate the various phases solutions (metabolites) through to solids (shell) (4) (13)C isotopic labelling and multidimensional NMR are combined to provide detailed assignment of metabolites and structural components in vivo. While not explicitly studied here the multiphase capabilities of the technique offer future possibilities to study kinetic transfer between phases (e.g. nutrient assimilation, contaminant sequestration), molecular binding at interfaces (e.g. drug or contaminant binding) and bonding across and between phases (e.g. muscle to bone) in vivo. Future work will need to focus on decreasing the spinning speed to reduce organism stress during analysis.